Kaimo jaunimas ir poezija - Kastanauskaitė, Laima (Knygotyra, 1973)
The present article gives a review of the research done in 1968 with the view of ascertaining the popularity of poetry among the village youth (aged 16 to 28) and the way it appreciates and understands this literary genre. The data were obtained on the basis of enquiries, interviews with the readers, analysis of library documentation and stock of books on poetry. It enabled to determine the interrelation between reading poetry and education, age, occupation, sex and family status of the youth. The enquired fall into three groups as far as poetry is concerned: 1) steady readers; 2) reading passively and ocassionally; 3) not interested in poetry. The main reasons for the lack of interest in poetry (indifference, absence of interest, ignorance, shortage of time) as well as the opinion both positive and negative of the youth on modern poetry are pointed out. The article lists the most popular Lithuanian poets, Russian poets, poets of the other nationalities of the U.S.S.R. and foreign poets. In most cases only classic poets and in Lithuanian literature – best modern poets are listed. The main criterion is folk character, simplicity, profound ideas.It is stressed that among other factors stimulating interest in poetry very important is the improvement of stocking rural libraries with collections of poetry.